Analisis Penggunaan Media Permainan KonselOpoly Quest pada Penerimaan Diri Siswa sebagai Aspek Aktualisasi Diri dalam Layanan Bimbingan dan Konseling - Raysa Nazwa Putri; Ririanti Rachmayanie Jamain; Hendro Yulius Suryo Putro (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
Several tenth-grade students at State Senior High School 12 Banjarmasin still demonstrated suboptimal self-acceptance, as reflected in their lack of confidence in expressing their opinions, feelings of embarrassment when expressing themselves, and difficulty accepting their own strengths and weaknesses. These conditions indicate the need for guidance and counseling services that promote students’ active participation through interactive learning media. This study aimed to describe the use of the KonselOpoly Quest game as a medium in guidance and counseling services to support students’ self-actualization, particularly in the aspect of self-acceptance, at State Senior High School 12 Banjarmasin. This study employed a qualitative approach with a descriptive research design. The participants consisted of one guidance and counseling teacher, one vice principal, and two tenth-grade students at State Senior High School 12 Banjarmasin. Data were collected through interviews, observations, and documentation and were analyzed using the Miles and Huberman model, which included data reduction, data display, and conclusion drawing. The trustworthiness of the data was ensured through source triangulation and technique triangulation. The findings showed that the use of the KonselOpoly Quest game encouraged students’ active participation during the guidance and counseling sessions. Based on the interview and observation results, students demonstrated greater confidence in expressing their opinions, began to recognize their strengths and weaknesses, and showed greater respect for their peers. These findings indicate that the KonselOpoly Quest game has the potential to support the implementation of guidance and counseling services by facilitating the development of students’ self-acceptance as one aspect of self-actualization.